Trauma and Existentialism in Cormac McCarthy’s The Road (2006)1 - Laguarta Bueno, Carmen (Nordic Journal of English Studies, 2019)
Since its publication in 2006, The Road has attracted the attention of many academics. The book has been understood by some as a conceited response to the terrorist attacks on the World Trade Center of September 11, 2001. Although the novel undoubtedly shares some of the characteristics which are typical of 9/11 novels, approaching it exclusively from this perspective can lead to a very narrow reading because, as I aim to show in this paper, the message that the novel conveys goes beyond one of non-violence. This paper analyzes the novel from the combined perspectives of trauma studies and Camus’ existentialism and shows that the novel’s strength lies in both the portrayal of the emotional consequences of a collective trauma and the existentialist message that it conveys in the face of devastation, while also offering reverberations of our (preapocalyptic) times.